2004
DOI: 10.1093/jb/mvh048
|View full text |Cite
|
Sign up to set email alerts
|

Secondary-Structure Analysis of Proteins by Vacuum-Ultraviolet Circular Dichroism Spectroscopy

Abstract: The vacuum ultraviolet circular dichroism (VUVCD) spectra of 15 globular proteins (myoglobin, hemoglobin, human serum albumin, cytochrome c, peroxidase, alpha-lactalbumin, lysozyme, ovalbumin, ribonuclease A, beta-lactoglobulin, pepsin, trypsinogen, alpha-chymotrypsinogen, soybean trypsin inhibitor, and concanavalin A) were measured in aqueous solutions at 25 degrees C in the wavelength region from 260 to 160 nm under a high vacuum, using a synchrotron-radiation VUVCD spectrophotometer. The VUVCD spectra below… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
98
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(103 citation statements)
references
References 0 publications
5
98
0
Order By: Relevance
“…There is still much to be done to assess the quality of matrix method calculations in the vacuum-UV and the extent to which they agree with experimental observations around 165 nm. 58,59 Our results also have some bearing on the deep-UV, as the transitions from the bonding p molecular orbital to the antibonding orbital are calculated to occur around 130 nm. The electric transition dipole moments of the local p nb ?p* and local p b ?p* transitions are perpendicular to one another.…”
Section: Charge Transfer Transitionsmentioning
confidence: 60%
See 1 more Smart Citation
“…There is still much to be done to assess the quality of matrix method calculations in the vacuum-UV and the extent to which they agree with experimental observations around 165 nm. 58,59 Our results also have some bearing on the deep-UV, as the transitions from the bonding p molecular orbital to the antibonding orbital are calculated to occur around 130 nm. The electric transition dipole moments of the local p nb ?p* and local p b ?p* transitions are perpendicular to one another.…”
Section: Charge Transfer Transitionsmentioning
confidence: 60%
“…Several recent studies have indicated the presence of features in the CD spectra of proteins around 165 nm. 58,59 There has been some speculation in the literature over the years as to the nature of the electronic transitions that might lead to these bands around 165 nm. Suggestions have included excitations to an antibonding r orbital, from either the higher-energy lone pair orbital on oxygen, nr*, or from the nonbonding p molecular orbital, pr*.…”
Section: Charge Transfer Transitionsmentioning
confidence: 99%
“…5) because VUVCD spectroscopy is a powerful technique for analyzing the secondary structures of proteins. 32,33) The spectrum exhibited a positive peak around 195 nm and two negative peaks around 220 and 170 nm, indicating that the recombinant ChiW-SLHd folded with some α-helix and β-stranded structures. The α-helix and β-strand contents of ChiW-SLHd estimated by using the SELCON3 program and the VUVCD spectrum down to 168 nm showed 22.8 and 29.1%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The details of the optical devices, sample cell, and data acquisition of the spectrophotometer were described previously. [30][31][32][33] The enzyme (141 μM) was prepared in buffer containing 10 mM sodium phosphate, pH 7.4. The secondary structure contents of ChiW-SLHd were estimated using the SELCON3 program 34) and the VUVCD spectra of the 31 reference proteins with known X-ray structures.…”
Section: Genetic Analysismentioning
confidence: 99%
See 1 more Smart Citation